2015
DOI: 10.2134/cftm2015.0122
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Glyphosate‐ and Imazapic‐Resistant Palmer Amaranth (Amaranthus palmeri) in Florida

Abstract: Herbicide‐resistant Palmer amaranth (Amaranthus palmeri S. Wats.) is the most troublesome weed in Florida cotton (Gossypium hirsutum L.) and peanut (Arachis hypogaea L.) production. In 2012, Palmer amaranth populations were surveyed to document the extent and level of resistance to glyphosate and imazapic. Mature seedheads were sampled at 31 locations in the northwest region of Florida where cotton and peanut are predominantly produced, and in the north‐central region of Florida that mainly consists of peanut … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Some of the putative genes flanking the EPSPS cassette had functions related to stress responses and DNA replication and mobility. Furthermore, GR populations in the southeastern United States have been reported having multiple resistance, especially to ALS-inhibiting herbicides (Berger et al 2015), so selection forces affecting adaptive traits could have influenced GR populations even when herbicides with other mechanisms of action were used. Although understanding secondary effects of herbicide-resistance traits is important, we must not ignore the fact that evolutionary adaptations might occur rapidly in agroecosystems, and weeds might be able to evolve compensatory mechanisms to disadvantages generated when herbicide resistance first evolves.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the putative genes flanking the EPSPS cassette had functions related to stress responses and DNA replication and mobility. Furthermore, GR populations in the southeastern United States have been reported having multiple resistance, especially to ALS-inhibiting herbicides (Berger et al 2015), so selection forces affecting adaptive traits could have influenced GR populations even when herbicides with other mechanisms of action were used. Although understanding secondary effects of herbicide-resistance traits is important, we must not ignore the fact that evolutionary adaptations might occur rapidly in agroecosystems, and weeds might be able to evolve compensatory mechanisms to disadvantages generated when herbicide resistance first evolves.…”
Section: Resultsmentioning
confidence: 99%
“…Palmer amaranth has also evolved resistance to glyphosate, the most widely used herbicide in agronomic crops in the United States. Although the first report of glyphosate-resistant (GR) Palmer amaranth originated in the state of Georgia (Culpepper et al 2006), since 2008 there have been confirmed cases of GR populations in Alabama, Arkansas, Florida, Mississippi, Missouri, New Mexico, North Carolina, South Carolina, and Tennessee (Berger et al 2015; Heap 2017; Mohseni-Moghadam et al 2013; Norsworthy et al 2008).…”
mentioning
confidence: 99%
“…The first confirmed case of glyphosate-resistant (GR) Palmer amaranth was reported in Georgia in 2004 (Culpepper et al 2006). Since then, GR Palmer amaranth populations have been identified throughout the United States, most recently in Florida (Berger et al 2015a; Heap 2016). As other herbicides have been used to manage GR populations, Palmer amaranth resistance has continued to increase and currently encompasses six different mechanisms of action (Heap 2016).…”
mentioning
confidence: 99%
“…This weed is of major concern to growers due to its aggressive growth habit and high seed production. Recently, the evolution of herbicide resistance has made Palmer amaranth even more difficult to manage (Berger et al 2015;Gaeddert et al 1997;Sellers et al 2003;Wise et al 2009). …”
mentioning
confidence: 99%
“…This weed is of major concern to growers due to its aggressive growth habit and high seed production. Recently, the evolution of herbicide resistance has made Palmer amaranth even more difficult to manage (Berger et al 2015; Gaeddert et al 1997; Sellers et al 2003; Wise et al 2009). A competitive species with high seed production, Palmer amaranth significantly affects peanut yields if not controlled early in the season.…”
mentioning
confidence: 99%